Sins for some, virtues for others: Media coverage of investment banks' misconduct and adherence to professional norms during the financial crisis. (September 2019) - Roulet, Thomas J
Why does professional misconduct persist in the face of media scrutiny? In this study, we explain how professional norms can be at odds with societal norms and how the behaviours they trigger can be perceived as misconduct. Most audiences tend to disapprove of wrongdoings, but specific stakeholders may interpret this disapproval as an indication of the focal organization's level of adherence to professional norms. Building on mixed methods, we explore the case of the investment banking industry during the financial crisis and suggest that corporate customers were favourably biased by the reporting of banks' misconduct in the print media as they linked it to the banks' quality of service. We capture the extent to which banks are associated with misconduct, signalling their adherence to negatively perceived professional norms. We then look at how such signalling affects the likelihood for banks to be invited into initial public offerings syndicates. Our findings show that the more banks are disapproved of for their wrongdoings, the more likely they are to be selected to join a syndicate. This study suggests that the coverage of misconduct can actually act as a positive signal providing banks with incentives to engage in what is broadly perceived as professional misconduct.